Distribusi Spasial Salinitas Laut Dari Citra Satelit Aquarius Di Samudera Hindia dan Hubungannya Dengan IOD - Maharta, I Putu Ranu Fajar; As-syakur, Abd. Rahman (Journal of Marine and Aquatic Sciences, 2023)
In the Indian Ocean there is a climatological oscillation phenomenon known as the India Ocean Dipole (IOD). IOD is a phenomenon that occurs due to the interaction between the atmosphere and the sea and is indicated by the presence of sea surface temperature anomalies in the western and eastern Indian Ocean. The IOD phenomenon can affect several physical-chemical parameters, one of which is salinity. To obtain salinity data, Aquarius satellite imagery is used, considering that it is very difficult to collect data in-situ. This study aims to conclude the pattern of distribution of the average salinity in the Indian Ocean every month, the rental pattern of the IOD correlation to the salinity in the Indian Ocean, and investigate the salinity anomaly that occurs during positive IOD cases in August 2012 and negative IOD cases in August 2012. June 2013. Salinity in the Indian Ocean differs between the west and east, and changes every month following the seasons that occur in the tropics. The Indian Ocean Dipole (IOD) is very influential on the distribution of salinity in the Indian Ocean because it has a fairly high correlation in almost the entire Indian Ocean. IOD causes salinity anomalies throughout the Indian Ocean, especially in the central part, when positive IOD, the salinity in the middle of the Indian Ocean will decrease, while when negative IOD, the salinity will increase.